An Empirical Evaluation of Regression Testing Based on Fix-Cache Recommendations - Engström, Emelie; Runeson, Per; Wikstrand, Greger (2010 Third International Conference on Software Testing, Verification and Validation, 2010)
Background: The fix-cache approach to regression test selection was proposed to identify the most fault-prone files and corresponding test cases through analysis of fixed defect reports. Aim: The study aims at evaluating the efficiency of this approach, compared to the previous regression test selection strategy in a major corporation, developing embedded systems. Method: We launched a post-hoc case study applying the fix-cache selection method during six iterations of development of a multi-million LOC product. The test case execution was monitored through the test management and defect reporting systems of the company. Results: From the observations, we conclude that the fix-cache method is more efficient in four iterations. The difference is statistically significant at α = 0.05. Conclusions: The new method is significantly more efficient in our case study. The study will be replicated in an environment with better control of the test execution.